The Analysis of The Absorption Capabilities of The Heavy Metal Mercury (Hg) in Mangrove Crab (Scylla serrata), Mangrove Snail (Telescopium telescopium) and Mangrove Clams (Polymesoda erosa) - Irsan, Irsan; Male, Yusthinus T.; Koto, Saifuddin; Mangesa, Rosita; Ismail, Irwan; Nuraisah, Siti; Kabau, Widyawati; Banjar, Firman (Indonesian Journal of Chemical Research, 2025)
Mercury is a neurotoxic heavy metal with high bioaccumulation ability in aquatic biota, such as mangrove crabs (Scylla serrata), mangrove snails (Telescopium telescopium), and mangrove mussels (Polymesoda erosa), which are widely consumed by humans, and used as bioindicators of pollution. This study aimed to analyze the effect of mercury solution concentration and species differences on mercury absorption in the three biota. The method used was experimental treatment with mercury concentrations of 1 ppm, 5 ppm, 10 ppm, and control. Samples were analyzed using the AAS Cold Vapor method at the IPB Bogor Proling Laboratory. Data were analyzed descriptively and inferentially using two-way Anova with an α level of 0.05, followed by the Duncan Test if the hypothesis was accepted. Research data will be processed using SPSS 26.0 software. The results showed that mercury concentration and species differences influenced the ability to absorb mercury. Mangrove clams had the highest mercury accumulation compared to mangrove snails and mangrove crabs, especially in the 5 ppm and 10 ppm treatments. The highest mercury exposure occurred on the second day of observation.